Mubarak Al-Sabah : the foundation of Kuwait - Al-Sabah, S. M. (I.B. Tauris, 2014)
Exploration of the life, personality, and politics of the man who ruled Kuwait from 1896 to 1915, especially in areas of the construction of the state and its political boundaries and international relations.